Presentation and management of pediatric elbow septic arthritis: Case series - Kılıç, Bülent; Agar, Anıl (Journal of Surgery and Medicine, 2020)
Aim: Septic arthritis is an emergency orthopedic situation, and septic arthritis of the elbow is rarely seen. The aim of this study was to evaluate the clinical and radiological determinants of septic arthritis of the elbow and review the mid-term clinical results. Methods: A case-series study was conducted on patients who visited a tertiary pediatric hospital between January 2015-January 2017, were diagnosed with septic arthritis of the elbow, and treated with drainage and debridement. All evaluations included obtaining a thorough history, physical examination, and radiological and laboratory workup. In the laboratory tests, full blood count, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), and blood culture were examined. Mayo scores of the elbows were evaluated in the last follow-up visit. Results: Five patients (5 elbows) including 3 males and 2 females with a mean age of 79 months (2-161 months) were included in this case-series. All patients presented with pain, signs of local inflammation (swelling, redness, increased heat) and fever (>38.5°). All patients had leukocytosis (leukocyte count>11,000), along with elevated CRP and ESR levels. Their mean CRP value during hospitalization was 110.2 (range: 17.5-285) and the mean ESR level was 46 (range: 24-85). The patients were followed up for a mean of 47 months (range: 31-58 months). At the final follow-up examination, the mean Mayo Elbow Performance Score of all the patients was 82.3 (range: 79-85), which was considered a good outcome. Conclusion: Septic arthritis should always be kept in mind in patients presenting to the Emergency Department with severe elbow function restriction together with fever, redness, swelling and no significant trauma history. To obtain successful clinical results, early debridement, irrigation, antibiotics use are important.